1985
DOI: 10.1099/00221287-131-8-2047
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Pigment Esters of Xanthomonas juglandis (campestris)

Abstract: Separation of the pigment esters of Xanthomonas juglandis (campestris) on silica gel columns yielded four bands. Two of the bands, esters 1 and 2, made up over 95% of the mixture. Both esters were phospholipids, with ester 1 containing the alcohol moieties glycerol and sorbitol, and ester 2 only glycerol. Both appeared to be mixtures containing different xanthomonadin pigment molecules but the results suggested that ester 1 consisted of one pigment molecule esterified to glycerophosphoryl sorbitol, whereas est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…D). This is highly consistent with previous findings that although there is substantially more chlorine than bromine in the environments, no natural occurrence of chlorinated relatives of the xanthomonadin pigments have yet been observed (Starr et al, ; Aririatu and Kester, ). Xcc probably has the unusual ability to scavenge bromine from its environments (including plants, soil and culture media) for xanthomonadin biosynthesis.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…D). This is highly consistent with previous findings that although there is substantially more chlorine than bromine in the environments, no natural occurrence of chlorinated relatives of the xanthomonadin pigments have yet been observed (Starr et al, ; Aririatu and Kester, ). Xcc probably has the unusual ability to scavenge bromine from its environments (including plants, soil and culture media) for xanthomonadin biosynthesis.…”
Section: Resultssupporting
confidence: 93%
“…This is further supported by the previous findings that that pigB ( xanB1 and xanB2 ) mutant supernatant extracts stimulated a 10‐fold greater extracellular enzyme production in rpfF mutants than the extracts from the parent strain (B‐24) (Poplawsky et al, ). In addition, Aririatu and Kester () proposed a sorbitol moiety‐containing structure for xanthomonadins. The present study suggests that the glycosyltransferase encoded by the gene xanK is responsible for transferring the sugar donor to xanthomonadin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…jug1andis. 207 By enzymatic and chemical hydrolysis and n.m.r. spectrometric analysis of the fragments, a major phosphoglycolipid from the Grampositive bacterium Deinococcus radiodurans was identified as the 2'-0- ( I ,2-diacyl-sn-glycero-3-phospho)-3'-0-(a-~-galacto-sy1)-N-D-glyceroylalkenamine (3).234 When E. coli was cultured in the presence of 600 mM D-mannitol, it synthesized phospha-0 0…”
Section: Glycophospholipidsmentioning
confidence: 99%
“…A characteristic feature of Xanthomonas is the production of yellow, membrane-bound pigments called xanthomonadins 4 . These pigments are mixtures of unusual brominated, aryl-polyene esters 5 6 . A previous study conducted by Poplawsky and Chun 7 has shown that xanthomonadin production in Xanthomonas is regulated by a diffusible factor (DF).…”
mentioning
confidence: 99%